Harnessing Agricultural Trade for Sustainable Development: Vanuatu Cocoa and Coconut - United Nations Conference on Trade; Development (United Nations, 2020)
The study builds on the National Green Export Review (NGER) of Vanuatu and leverages UNCTAD expertise in key analytical areas, including non tariff measures, voluntary sustainability standards (VSS), the trade agriculture gender nexus, and pro poor structural rural diversification through trade. Invaluable support was provided by the Government of Vanuatu, in particular, the Department of Industry, which generously shared information, facilitated multi stakeholder consultations and reviewed the final draft. The information in this report has been gathered from various sources, including interviews with key stakeholders in the country. To this purpose, missions were carriedout in Port Vila, Vanuatu, in 2017 and 2018. Interviews were conducted with public and private stakeholders, including representatives from the Department of Industry, the Department of Agriculture and Rural Development, the Department of Women’s Affairs, the National Statistics Office, the Government Chief Information Officer, the private sector, International Organisations and the donor community.